Hybridisation-based target enrichment of phenology genes to dissect the genetic basis of yield and adaptation in barley - Hill, C.; Angessa, T.; McFawn, L.; Wong, D.; Tibbits, J.; Zhang, X.; Forrest, K.; Moody, D.; Telfer, P.; Westcott, S.; Diepeveen, Dean; Xu, Y.; et al. (Wiley-Blackwell Publishing Ltd., 2018)
Plant Biotechnology Journal published by Society for Experimental Biology and The Association of Applied Biologists and John Wiley & Sons Ltd. Barley (Hordeum vulgare L.) is a major cereal grain widely used for livestock feed, brewing malts and human food. Grain yield is the most important breeding target for genetic improvement and largely depends on optimal timing of flowering. Little is known about the allelic diversity of genes that underlie flowering time in domesticated barley, the genetic changes that have occurred during breeding, and their impact on yield and adaptation. Here, we report a comprehensive genomic assessment of a worldwide collection of 895 barley accessions based on the targeted resequencing of phenology genes. A versatile target-capture method was used to detect genome-wide polymorphisms in a panel of 174 flowering time-related genes, chosen based on prior knowledge from barley, rice and Arabidopsis thaliana. Association studies identified novel polymorphisms that accounted for observed phenotypic variation in phenology and grain yield, and explained improvements in adaptation as a result of historical breeding of Australian barley cultivars. We found that 50% of genetic variants associated with grain yield, and 67% of the plant height variation was also associated with phenology. The precise identification of favourable alleles provides a genomic basis to improve barley yield traits and to enhance adaptation for specific production areas.